Enhancing Text Messages with a Combination of Vigenère Cipher and One Time Pad Using Random Key LFSR - Ibezato Zalukhu, Anzas; Sitorus, Zulham; Suhardiansyah, Suhardiansyah; Septiani, Nadya (CV. Utility Project Solution, 2024)
In today's global era, the development of information systems is rapidly advancing and becoming increasingly sophisticated, with nearly all elements utilizing information and communication technology in their daily activities. One frequent activity is the transmission or exchange of data over the internet. However, this advancement also raises concerns about the security of messages or data being sent. To mitigate the risk of message misuse, cryptographic techniques can be used to maintain data or message confidentiality by encrypting the information before transmission. This research aims to combine the Vigenère cipher algorithm with a one-time pad using a random key generated by a linear feedback shift register (LFSR) method to enhance the security of text messages. The research methodology involves generating a public key for the One-Time Pad algorithm using LFSR. The encryption process is initially performed with the Vigenère cipher, and the resulting encrypted message is further encrypted using the one-time pad with a key generated by the LFSR method. This algorithm is implemented using the Visual Basic programming language. The research findings indicate that the combination of the two algorithms, with the random key generated by the LFSR for the One-Time Pad, is capable of enhancing text message security by producing random and unique ciphertexts. By using Modulo 256 and ASCII conversion, random ciphertexts can be generated, thereby reducing the likelihood of message breaches. Additionally, this research provides further insights into the process of text message encryption and decryption.